2018
DOI: 10.1155/2018/7208031
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of a Corroded Reinforce Concrete Frame Structure Using Pushover Method

Abstract: SAP2000 software was used to build the finite element model of a six-storey-three-span reinforced concrete (RC) frame structure.e numerical simulation of the seismic performance of the RC frame structure incorporating different levels of rebar corrosion was conducted using pushover analysis method. e degradation characteristics of the seismic performance of the corroded structure under severe earthquake were also analyzed. e results show that the seismic performance of the RC frame decreased significantly due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To determine the development of the plastic hinges, a force‐displacement curve composed by two segments is used: linear segment A–B and nonlinear segment B–C 20,32,49 (see Figure 9). The intermediated levels are identified, consistent to the Figure 9b, by: immediate occupancy IO (yellow color), life safety LS (red color), collapse prevention CP (magenta color).…”
Section: Analysis and Deterministic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the development of the plastic hinges, a force‐displacement curve composed by two segments is used: linear segment A–B and nonlinear segment B–C 20,32,49 (see Figure 9). The intermediated levels are identified, consistent to the Figure 9b, by: immediate occupancy IO (yellow color), life safety LS (red color), collapse prevention CP (magenta color).…”
Section: Analysis and Deterministic Resultsmentioning
confidence: 99%
“…For determining demand displacements of PSWSs, a nonlinear static analysis (NSA) is used in current practice consistent to design codes and standards 6–10 . There is an extensive literature on pushover analysis—a typical NSA—but most of these are applied to constructions different from PSWSs 11–23 …”
Section: Introductionmentioning
confidence: 99%
“…Cyclic experimental tests on RC columns [1][2][3][4][5][6] were carried out considering different corrosion levels. Based on available experimental findings, numerical models were developed to perform seismic vulnerability assessment of corroded RC buildings 7,8 and bridges. [9][10][11][12] The process of chloride-induced corrosion includes three main phases that are initiation, propagation, and deterioration phase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that every plastic hinge had been produced at performance levels that fell below the immediate occupancy limit. Zhang, et al [10] Analyzed six storey building to estimate its resistance to seismic events by utilizing SAP2000 software. The pushover analysis was used to estimate the storey drift and roof displacement.…”
Section: Introductionmentioning
confidence: 99%